Analysis Metaphors Lyric Song In Petal For Armor By Hayley Williams - Febrian, Gilang (EDUJ : English Education Journal, 2023)
This thesis aims to analysis the use of conceptual metaphors in the songs on the album Petals for Armor by Hayley Williams by focusing on discussing the meaning that is in each song. This study uses a qualitative analysis process on the lyrics chosen based on the use and diversity of metaphors contained in the text of the song lyrics. The data were analysis using a descriptive-analytical approach, which involved identifying and classifying the conceptual metaphors that appear in the lyrics of the song. Based on the results of this thesis analysis, there are 21 conceptual metaphors found in the song lyrics in the Petals for Armor album. The results of the analysis show that the album Petals for Armor contains various types of conceptual metaphors that are used to describe and express the author's experience to be understood by listeners through writing metaphors in each of the song lyrics.